Salsakrup! / Muhammad Azril Afiq Azli - Azli, Muhammad Azril Afiq (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
For my client PapaHomemade Sambal Bilis Garing, a fantastic dried anchovy sambal store founded by Noor Efandi bin Abdul Rashid in 2015 at his hometown in Taman Tun Sardon in Penang, my project involves producing and designing the SalsaKrup! edition flavoured dried anchovy sambal. PapaHomemade was founded by Mr. Efandi as a side gig to supplement his income. From there, the concept developed into a successful sambal business as a consequence of high demand for the original, specially-tasting recipe. The company is quite skilled at producing sambal and bite-sized food items. The well-known Sambal Bilis Garing is the product that sells the best. The logo for the recently added flavours to the brand is a complex construction that incorporates the identities of the ingredients and anchovies, The tagline 'Pedas Berdansa" conveys the joy and emotions of customers who sampled the novel flavours, guaranteeing that they would be returning for more. Just like others say, 'It's amazing! You might even start dancing." As previously mentioned, Sambal Salsa Tomyam, Sambal Salsa Cili Merah, and Sambal Salsa Cili Hijau are the new flavoured sambal that is available at PapaHomemade, These additional flavours play with the intensity of the heat and the distinct flavour that results from combining them with the dried anchovies. The creation of the packaging and ancillary marketing materials comes after the creation of these new tastes since they are crucial in spreading awareness of these flavours among consumers.